Factors affecting haemoglobin dynamics in African children with acute uncomplicated Plasmodium falciparum malaria treated with single low-dose primaquine or placebo - Onyamboko, MA; Olupot-Olupot, P; Were, W; Namayanja, C; Onyas, P; Titin, H; Baseke, J; Muhindo, R; Kayembe, DK; Ndjowo, PO; Basara, BB; Okalebo, CB; et al. (BioMed Central, 2023)
Background Single low-dose primaquine (SLDPQ) effectively blocks the transmission of Plasmodium falciparum malaria, but anxiety remains regarding its haemolytic potential in patients with glucose-6-phopshate dehydrogenase (G6PD) deficiency. We, therefore, examined the independent effects of several factors on haemoglobin (Hb) dynamics in falciparum-infected children with a particular interest in SLDPQ and G6PD status. Methods This randomised, double-blind, placebo-controlled, safety trial was conducted in Congolese and Ugandan children aged 6 months–11 years with acute uncomplicated P. falciparum and day (D) 0 Hbs ≥ 6 g/dL who were treated with age-dosed SLDPQ/placebo and weight-dosed artemether lumefantrine (AL) or dihydroartemisinin piperaquine (DHAPP). Genotyping defined G6PD (G6PD c.202T allele), haemoglobin S (HbS), and α-thalassaemia status. Multivariable linear and logistic regression assessed factor independence for continuous Hb parameters and Hb recovery (D42 Hb > D0 Hb), respectively. Results One thousand one hundred thirty-seven children, whose median age was 5 years, were randomised to receive: AL + SLDPQ (n = 286), AL + placebo (286), DHAPP + SLDPQ (283), and DHAPP + placebo (282). By G6PD status, 284 were G6PD deficient (239 hemizygous males, 45 homozygous females), 119 were heterozygous females, 418 and 299 were normal males and females, respectively, and 17 were of unknown status. The mean D0 Hb was 10.6 (SD 1.6) g/dL and was lower in younger children with longer illnesses, lower mid-upper arm circumferences, splenomegaly, and α-thalassaemia trait, who were either G6PDd or heterozygous females. The initial fractional fall in Hb was greater in younger children with higher D0 Hbs and D0 parasitaemias and longer illnesses but less in sickle cell trait. Older G6PDd children with lower starting Hbs and greater factional falls were more likely to achieve Hb recovery, whilst lower D42 Hb concentrations were associated with younger G6PD normal children with lower fractional falls, sickle cell disease, α-thalassaemia silent carrier and trait, and late treatment failures. Ten blood transfusions were given in the first week (5 SLDPQ, 5 placebo). Conclusions In these falciparum-infected African children, posttreatment Hb changes were unaffected by SLDPQ, and G6PDd patients had favourable posttreatment Hb changes and a higher probability of Hb recovery. These reassuring findings support SLDPQ deployment without G6PD screening in Africa. Trial registration The trial is registered at ISRCTN 11594437.